Multiple Equilibria and Minimum Wages in Labor Markets with Informational Frictions and Heterogeneous Production Technologies - Gerard J. van den Berg (Institute for the Study of Labor (IZA), 2003)
It is often argued that a mandatory minimum wage is binding only if the wage density displays a spike at it. In this paper we analyze a model with search frictions and heterogeneous production technologies, in which imposition of a minimum wage affects wages even though, after imposition, the lowest wage in the market exceeds the minimum wage. The model has multiple equilibria as a result of the fact that the reservation wage of the unemployed and the lowest production technology in use affect each other. Imposition of a minimum wage may improve social welfare.
Keywords: J42; D83; J3; C72; J6; 330; wages; productivity; job search; unemployment; imperfect information; equilibrium; labor market policy; matching; congestion; Arbeitsmarkt; Mindestlohn; Arbeitsuche; Gleichgewichtstheorie; Theorie